THE COMMUNIST PARTY OF CHILE AND POLICIES ALLIANCE: POPULAR FRONT TO THE NATIONAL UNION AGAINST FASCISM, 1935-1943 - Venegas Valdebenito, Hernán (Revista de Historia Social y de las Mentalidades, 2024)
Since the mid 1930s the Chilean Communist  Party defined a policy alternative to its  proposal for achieving revolution in Chile, in  stages and gradually. This fundamental change  in the future of the organization resulted in  the long term, in a series of frictions within  the Chilean left during that decade. The  party developed the belief that significant  social change is the result of qualitative  progress in a democratic process of changes  implemented from state institutions. This  meant the dismissel, as unworkable and risky,  flows the traditional stance of the Chilean  left immediate leap to a socialist revolution.  This also meant the relegation of military of  strategy as a route to empowerment, at least  until the conditions of enlargement of the  democratic sistem were mature for the masses  rise to power.
Keywords: communist; alliance; popular front; masses